MMP3 mediates E2-induced bovine endometrial cell proliferation by releasing HB-EGF - Al-Nur Md. Iftekhar RAHMAN; Chi Sun YUN; Amir SALAMA; Md. Rafikul ISLAM; M. A. M. Yahia KHANDOKER; Toru TAKAHASHI; Kei MIYAMOTO; Nobuhiko YAMAUCHI (The Journal of Reproduction and Development, 2025)
Cyclic cell proliferation and endometrial remodeling during the estrous cycle are important for maintaining normal endometrial function. However, the regulatory mechanisms underlying this cell proliferation have not yet been elucidated. In this study, the function of matrix metalloproteinase 3 (MMP3) on endometrial cell proliferation was analyzed. Gene expression in bovine endometrial stromal (BES) and epithelial (BEE) cells was analyzed using qPCR. The protein expression of MMP3 and heparin-binding EGF-like growth factor (HB-EGF) was analyzed using casein zymography and western blotting, respectively. Cell proliferation was analyzed using an automated cell counter. The results revealed that MMP3 was highly expressed at the follicular stage compared to that at the luteal and implantation stages. Estrogen (E2) increased the gene expression and release of MMP3 protein in BES in vitro, whereas progesterone (P4) and interferon alpha (IFNα) decreased mRNA and protein expression. E2 also increased the proliferation of BES, but the inhibitors of MMP3 and epidermal growth factor receptor (EGFR) inhibited the proliferation induced by E2. Furthermore, E2 increased the release of HB-EGF from BES, whereas the MMP3 inhibitor suppressed this release. The effect of E2 on BEE cell proliferation was not reported. However, the conditioned medium of BES treated with E2 increased BEE cell proliferation but was inhibited by an EGFR inhibitor. E2 induced MMP3 protein expression and promotes HB-EGF release from BES. These results suggest that MMP3 is involved in endometrial cell proliferation during the follicular stage.